Systemic determinants of modern gravitational processes in the geo-economic space - Zoryana Lutsyshyn; Natalia Kravchuk (International Economic Policy, 2015)
From the compositional point of view, research on this topic has revealed two main directions: (1) an analysis of global development asymmetry that has activated gravitational processes in geo-economic space; and (2) a direction that focuses on the profound study of the causes for heterogeneity in geo-economic space and divergence in global development under the influence of gravitational factors of nature on the endogenousexogenous axis. Systemic determinants of gravitational processes are revealed in geo- economic space and the asymmetry of global activate ravitional processes in geo-economic space are observed, and methodological interconnectedness coinfluence of two complementary determinants of global development – convergence and divergence and the contradiction between them are examined, which at the same time underlie the inevitable internal contradictions of the process, creating conditions for further configuration of the «new globalization community», which is built on the principles of nonlinear dynamics and logic gravitational processes in geo-economic space.Taking into account the relevant uncertainties, the attention is focused on the isolation of several myths around which the debate that has important methodological significance in the context of the current global inter-system transformations is held. Geostrategic matrix divergence of global development is produced,which is based on techniques which incorporated cluster analysisthat are built on linguistic variables and integrated analysis of the key trends of country and global development geostrategic position of Ukraine in geo-economic space in the projection on the issues of global inter-system transformations isoutlined .It is proved that the level of gravity load increases in the deepening of the global asymmetries , and that the current global transformation is not yet complete, and polycentric new architecture geospace is not formed. In the near future we should expect the growth of gravitational processes in geo-economic space under the influence of fragmentation in information technology development countries, worsening energy problems, strengthening of the environmental risks and disasters, adverse trends sociodemographic. The divergence of global development will be strengthened as institutional «failure» and socio-cultural constraints. These aspects should be the subject of research and theoretical basis for the formation of new approaches to global development.